An Industry without Industrialization: The Political Economy of The Failure of Indonesiaâ€™s Auto Industry - Tai, Wan-Ping (JAS (Journal of ASEAN Studies), 2014)
The development of auto industry needs a series of related policies and conditions, including market, technology, management, basic infrastructure, etc. Several Southeast Asian countries are hoping to develop their auto industries in order to lead the development of other industries in their countries. Having the largest auto market in Southeast Asia, Indonesia is supposed to have more favorable conditions than Thailand and Malaysia on the development of auto industry. Unlike Malaysiaâ€™s auto industry that has its own national brand, Indonesia does not have a national auto brand, nor like Thailand as the largest auto exporting country in Southeast Asia, a Japanese scholar even contends that Indonesiaâ€™s auto industry is â€œtechnology-less industrializationâ€.Â Based on the above analysis, the paper argues that the failure of Indonesiaâ€™s auto industry has to do with the structural factors in Indonesiaâ€™s political economy.Â  This paper therefore will, by taking the perspective of political economy, explore the following four factors over the failure of Indonesiaâ€™s auto industry: (1) inappropriate state intervention, (2) distorted government-business relations, (3) failure to join international complementarities in the auto industry, and (4) ineffective management on globalization.